Laser weed seed control: challenges and opportunities - Andreasen, Christian; Vlassi, Eleni; Salehan, Najmeh; Johannsen, Kenneth S.; Jensen, Signe M. (Frontiers in Agronomy, 2024)
Farmers are greatly interested in reducing weed seeds in their fields to avoid unnecessary weed infestation. Autonomous vehicles equipped with plant recognition systems and lasers can be used to control weed plants and may therefore be used to as replacements or supplementbstitutes for herbicides and mechanical weed control. However, less is known about the ability of laser to control weed seeds. In this study, seeds of weeds (Alopecurus myosuroides, Anisantha sterilis, Avena fatua, Centaurea cyanus, Silene noctiflora) and crops (wheat (Triticum aestivum), maize (Zea mays)) were exposed to increasing dosages of laser energy. The species represented dicots and monocots with different seed sizes and morphology. We used a thulium-doped 50 W fiber laser with a wavelength of 2 µm and a diameter of 2 mm developed for weed control. The seeds were exposed to laser directly on the seed surface or after been covered with soil (2.5 and 5 mm). Small doses of energy (0.4 J mm-2 and 0.8 J mm-2) affected the germination ability of small seeds (S. noctiflora and C. cyanus) when the seeds were irradiated directly on the seed surface, and they were completely burned at the high doses (8.0 J mm-2 and 15.9 J mm-2). However, there was not a clear relationship between seed size and sensitivity to laser dose. Additionally, increasing the laser dose on the seed surface resulted in increasing infection of fungi. Seeds covered with soil were not affected by the laser treatments except C. cyanus seeds. Controlling large seeds on the ground while weed seedlings are controlled with laser robots seems realistic in the future. However, dosages higher than 16 J mm-2 is necessary to control large seeds.